(untitled) (Homoeopathy for All, 2026)
Varicose veins are a common vascular disorder characterized by dilated, elongated, and tortuous superficial veins, predominantly affecting the lower extremities. This condition arises due to valvular incompetence leading to venous hypertension. The present thesis explores the etiology, pathophysiology, clinical features, diagnosis, complications, and management of varicose veins, with a special emphasis on homoeopathic therapeutics. Homoeopathy, based on the principle of individualization, offers a holistic approach in managing varicose veins, particularly in early and moderate stages. This study integrates classical homoeopathic literature with modern medical understanding to provide a comprehensive overview.